PRAKIRAAN KEBUTUHAN ENERGI LISTRIK MENGGUNAKAN PEMROGRAMAN MATLAB PADA PLN DISTRIBUSI JAWA TENGAH CABANG YOGYAKARTA - Hani, Slamet (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2005)
To full fill the requirements of electric power to the customer economically, the company have to able to predict the requirements of electric power itself accurately. The study is aimed to see how multi linear regression works due to forecast con-sumption of electric power. There are five sectors of Daerah Istimewa Yogyakarta which has been research field, they are household, business, industrial, general and total sec-tors. The formulas are used and developed based on multi linear regression including the requirements itself. The main tool to support the analysis utilized Matlab (Matrix La-boratory) programming. The study succeeds to develop regression model for each sector.